A Touch of Doubt On Haptic Scepticism - Aumiller, Rachel (Studies and Texts in Scepticism, 2021)
Scepticism claims that there is always something that slips through the epistemologist's grasp.Drawing on the tradition of scepticism within continental philosophy, this volume discusses how the sense of touch uncovers contradictions within our knowledge of ourselves and the world. It questions what we can know through touch, what we can know about touch itself, and how our experience of touching throws us into doubt.